Religious Narratives during the Pandemic: Transitivity Analysis of Covid-19 Hoax Discourse on Indonesian Social Media - Oktavianus Oktavianus; Hetti Waluati Triana; Muhammad Ilham; Annisa Khairunnisa (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
Many studies have been carried out on religious narratives that go hand in hand with the Covid-19 pandemic, but only focus on religious authority, religious attitudes and behavior, and the contributions of religious leaders. In fact, the religious dimension in the Covid-19 hoax circle is a form of social practice that contains a dialectical process. This article aims to reveal the hidden dialectical process in the lingual features of the Covid-19 hoax through Halliday’s transitivity analysis. This descriptive qualitative research data is in the form of lingual elements in the Covid-19 hoax content related to religious issues. Data was collected using documentation techniques on four website pages to fact-check Covid-19 news published throughout 2020-2021. Data collection was carried out by going through the stages of reading and observing, sorting, storing and printing, rereading, and determining research subjects. The data is then analyzed by taking the data reduction stage; display data; conclusion, and verification. The results showed that of the 121 data used as a corpus, 6 types of transitivity processes were found, namely (1) material processes, (2) mental processes, (3) relational processes, (4) verbal processes, (5) behavioral processes, and (6) existential process. The research findings provide a new perspective on the tendency of discourse producers to construct narratives about Covid-19 and religious issues. The research findings will have implications for efforts to educate the public about hoax issues around Covid-19. With the description of the exploitation of religious issues, it is hoped that the community will be aware and able to think critically in digesting information.